Construction Workers Help - Tami Deedrick (Mankato, MN, United States Capstone Press, 2014)
Construction workers build our homes, businesses, and stores. Learn about a construction worker's tools, workplace, and role in the community.
Keywords: PY UOI - How We Express Ourselves -- PY UOI - How We Express Ourselves; Community Helpers -- Community Helpers